Climate Change in Educational Experiences of University Teachers - Maldonado-González, Ana Lucía (2023)
Purpose. To explore and analyze the possibilities of integrating climate change (CC) in higher-level educational experiences with teachers from the Universidad Veracruzana (UV), at the Poza Rica-Tuxpan campus, Mexico. Due to its geographical location, the region is exposed to extreme hydrometeorological phenomena; there is physical and social vulnerability. Method. The study consisted of group interviews with teachers. They inquired about the threats associated with CC, identified them in their region, and how they approach the CC phenomenon in their academic activity and teaching practice. The dimension of attitudes from social representations theory is retaken as a substantive category; risk, vulnerability, and social resilience as formal categories were used as data-gathering tools in the study region. For the group interviews, a semi-structured guide was developed. The interviews were audio-recorded and transcribed verbatim, then analyzed using the content analysis technique. Results. Participants identify and address CC and other threats associated with this phenomenon in their educational experiences. A teaching practice committed to the environmental problem of its own context is recognized. Moreover, the link with other social, municipal, and community actors, who collaborate in educational practices to reduce vulnerabilities, promote risk management, and advance in the process of co-building social resilience, considering CC adaptation and mitigation measures. Conclusions. Educational action, thus, contributes to climate action, strengthening individual and collective capacities that are undoubtedly necessary to stop the current climate crisis.